Photoluminescence Redistribution of InGaN Nanowires Induced by Plasmonic Silver Nanoparticles - Talgat Shugabaev; Vladislav O. Gridchin; Sergey D. Komarov; Demid A. Kirilenko; Natalia V. Kryzhanovskaya; Konstantin P. Kotlyar; Rodion R. Reznik; Yelizaveta I. Girshova; Valentin V. Nikolaev; Michael A. Kaliteevski; George E. Cirlin (Nanomaterials, 2023)
Hybrid nanostructures based on InGaN nanowires with decorated plasmonic silver nanoparticles are investigated in the present study. It is shown that plasmonic nanoparticles induce the redistribution of room temperature photoluminescence between short-wavelength and long-wavelength peaks of InGaN nanowires. It is defined that short-wavelength maxima decreased by 20%, whereas the long-wavelength maxima increased by 19%. We attribute this phenomenon to the energy transfer and enhancement between the coalesced part of the NWs with 10–13% In content and the tips above with an In content of about 20–23%. A proposed Fröhlich resonance model for silver NPs surrounded by a medium with refractive index of 2.45 and spread 0.1 explains the enhancement effect, whereas the decreasing of the short-wavelength peak is associated with the diffusion of charge carriers between the coalesced part of the NWs and the tips above.